2020
DOI: 10.3892/ol.2020.11550
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of CT‑guided 125I brachytherapy in elderly patients with non‑small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) has become the most common cancer type and the leading cause of cancer-associated mortality worldwide. The aim of the present retrospective study was to evaluate the efficacy and safety of computed tomography (CT)-guided 125 I brachytherapy alone in elderly patients with NSCLC. A total of 26 elderly patients with NSCLC stage I-III who had an inoperable lesion or progressive disease following radio-chemotherapy were treated with CT-guided 125 I seed implantation for lung lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…125 I brachytherapy is known to be safe and effective in advanced cancer patients (11)(12)(13)(14)(15)(16)(17), and the multiple-needle parallel puncture method is the most common and widely used treatment regimen for 125 I brachytherapy (11)(12)(13)(14)(15)(16)(17)37). It requires multiple accessible puncture sites without obstruction, and is suitable for tumors with relatively regular shapes.…”
Section: Discussionmentioning
confidence: 99%
“…125 I brachytherapy is known to be safe and effective in advanced cancer patients (11)(12)(13)(14)(15)(16)(17), and the multiple-needle parallel puncture method is the most common and widely used treatment regimen for 125 I brachytherapy (11)(12)(13)(14)(15)(16)(17)37). It requires multiple accessible puncture sites without obstruction, and is suitable for tumors with relatively regular shapes.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine-125 ( 125 I) brachytherapy (BT) has become an important part of the comprehensive treatment of malignant tumors, such as prostate cancer, lung cancer, liver cancer, and bone metastases, because it involves low-dose continuous irradiation, satisfactory local effects, and strong repeatability [3][4][5][6]. Animal studies confirmed that 125 I BT can significantly inhibit squamous cell carcinoma [7].…”
Section: Purposementioning
confidence: 99%
“…Nevertheless, in the case of devices whose operation is based on electromagnetic fields that could be disturbed by external fields or objects involved in medical instruments near or inside the device, typical examples are static fixed-function wearable measuring tools-e.g., [27][28][29]active organ stimulation tools-e.g., [30,31]-and magnetic resonance imagers (MRI) used in image-guided therapies and interventions. Actually, these image-guided operations can use several types of imagers, e.g., [32][33][34][35][36][37][38]. Among these imagers, only two are free of ionizing radiation: the MRI and ultrasound imager (USI) [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%